2011
DOI: 10.1007/s10585-011-9415-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of metastasis using a non-volatile buffer

Abstract: The tumor microenvironment is acidic as a consequence of upregulated glycolysis and poor perfusion and this acidity, in turn, promotes invasion and metastasis. We have recently demonstrated that chronic consumption of sodium bicarbonate increased tumor pH and reduced spontaneous and experimental metastases. This occurred without affecting systemic pH, which was compensated. Additionally, these prior data did not rule out the possibility that bicarbonate was working though effects on carbonic anhydrase, and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…In particular, reduction of extracellular acidosis can increase the uptake and cytotoxic effects of weakly basic drugs, including doxorubicin. Interestingly, chronic ingestion of sodium bicarbonate solution was shown to enhance the capacity of doxorubicin to decrease the tumor size [166]. Specific inhibition of CA IX activity by indanesulfonamide enhanced the effect of tumor irradiation [79].…”
Section: Ca IX As a Therapy Targetmentioning
confidence: 99%
“…In particular, reduction of extracellular acidosis can increase the uptake and cytotoxic effects of weakly basic drugs, including doxorubicin. Interestingly, chronic ingestion of sodium bicarbonate solution was shown to enhance the capacity of doxorubicin to decrease the tumor size [166]. Specific inhibition of CA IX activity by indanesulfonamide enhanced the effect of tumor irradiation [79].…”
Section: Ca IX As a Therapy Targetmentioning
confidence: 99%
“…These new developments may also be advantageous for imaging purposes and may be applicable to solid tumors, ischemia, stroke, and infection [220,221,222]. Furthermore, to reduce the effects of acidosis on drug activity under acidic conditions, systemic buffer therapy has been proven to be effective in alkalizing the tumor microenvironment [223,224,225]. In several reports oral administration of buffers such as lysine, sodium bicarbonate, or 2-imidazole-1-yl-3-ethoxycarbonylpropionic acid (IEPA) was used to systemically buffer mice in order to reduce tumor growth and metastasis [223,224,225].…”
Section: Implications For Cancer Therapy and Chemopreventionmentioning
confidence: 99%
“…Furthermore, to reduce the effects of acidosis on drug activity under acidic conditions, systemic buffer therapy has been proven to be effective in alkalizing the tumor microenvironment [223,224,225]. In several reports oral administration of buffers such as lysine, sodium bicarbonate, or 2-imidazole-1-yl-3-ethoxycarbonylpropionic acid (IEPA) was used to systemically buffer mice in order to reduce tumor growth and metastasis [223,224,225]. Using systemic buffers may increase the activity of certain drugs that are normally inactive in such acidic environments [216,219].…”
Section: Implications For Cancer Therapy and Chemopreventionmentioning
confidence: 99%
“…Previously we have shown that an amino acid, lysine, reduces metastasis in a prostate cancer model, which we hypothesized occurs through buffering of peri-tumoral pH [32]. Lysine has three pKas and can be protonated at the side chain amino group, backbone amino group and carboxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…PC-3M cells were cultured as detailed previously [32]. In preparation for injection, PC-3M cells were trypsinized and washed once with sterile 1X PBS before being suspended at a concentration of 2.4 × 10 6 cells in 200 μL PBS.…”
Section: Methodsmentioning
confidence: 99%